Bioconcentration of chlorpyrifos in roots and foliage of plants of Cenchrus clandestinus (Hochst. ex chiov.) morrone, cultured in green house - Sara María Márquez Giron (Revista Facultad Nacional de Agronomía - Medellín, 2017)
The bio-concentration of the insecticide chlorpyrifos in grass Cenchrus clandestinus cultivated in green house was determined. The pesticide was applied in the culture solution and we carried out the monitoring of the concentration of the pesticide in foliage and root tissues during 72 h of exposure to the nutrient solution with 96, 192 and 288 mg L -1 of chlorpyrifos. Tissue samples were taken at 4, 24, 48 and 72 h. Removal of chlorpyrifos of foliage and grass root used the MI 48640 with a sensitivity of 0.01 ppm and the quantiscation was carried out by gas chromatography. During the study, it was possible to observe that chlorpyrifos is transported through the vascular system of plants in grass C. clandestinus in hydroponic cultivation, from the root to the foliage. In addition, it showed an increasing bioaccumulation in the tissues of roots and foliage. Bioaccumulation of chlorpyrifos was higher in the root 39.4 μg g -1 than in foliage 1.1 μg g -1 . Therefore, the use of this insecticide on livestock systems from high tropical areas represents a risk for cattle and other members of the dairy food chain.